Tracking Alternative Jet Fuel - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB’s Airport Cooperative Research Program (ACRP) Research Report 165: Tracking Alternative Jet Fuel provides guidance to airports on ways to track alternative jet fuels. As alternative jet fuels start to enter the supply chain, there may be a need to keep track of such fuel for technical, regulatory, and commercial reasons. In addition to the guidance, a greenhouse gas calculator and an alternative fuels inventory tracking spreadsheet compare different types of tracking mechanisms and evaluate their advantages and disadvantages, impediments to implementation, and potential impacts.Spreadsheet disclaimer: This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Commercial Aircraft Propulsion and Energy Systems Research: Reducing Global Carbon Emissions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The primary human activities that release carbon dioxide (CO2) into the atmosphere are the combustion of fossil fuels (coal, natural gas, and oil) to generate electricity, the provision of energy for transportation, and as a consequence of some industrial processes. Although aviation CO2 emissions only make up approximately 2.0 to 2.5 percent of total global annual CO2 emissions, research to reduce CO2 emissions is urgent because (1) such reductions may be legislated even as commercial air travel grows, (2) because it takes new technology a long time to propagate into and through the aviation fleet, and (3) because of the ongoing impact of global CO2 emissions.
Keywords: Space and Aeronautics; Environment and Environmental Studies

Transitioning Toward Sustainability: Advancing the Scientific Foundation: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In 1999 the National Academies of Sciences, Engineering, and Medicine released a landmark report, Our Common Journey: A Transition toward Sustainability, which attempted to “reinvigorate the essential strategic connections between scientific research, technological development, and societies’ efforts to achieve environmentally sustainable improvements in human well-being.”1 The report emphasized the need for place-based and systems approaches to sustainability, proposed a research strategy for using scientific and technical knowledge to better inform the field, and highlighted a number of priorities for actions that could contribute to a sustainable future.
Keywords: Environment and Environmental Studies

Electricity Use in Rural and Islanded Communities: Summary of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On behalf of the Quadrennial Energy Review (QER) Task Force, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on February 8-9, 2016, titled "Electricity Use in Rural and Islanded Communities." The objective of the workshop was to help the QER Task Force public outreach efforts by focusing on communities with unique electricity challenges. The workshop explored challenges and opportunities for reducing electricity use and associated greenhouse gas emissions while improving electricity system reliability and resilience in rural and islanded communities. This report summarizes the presentation and discussion of the workshop.
Keywords: Energy and Energy Conservation

Assessment of Approaches to Updating the Social Cost of Carbon: Phase 1 Report on a Near-Term Update - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The social cost of carbon (SCC) for a given year is an estimate, in dollars, of the present discounted value of the damage caused by a 1-metric ton increase in CO2 emissions into the atmosphere in that year; or equivalently, the benefits of reducing CO2 emissions by the same amount in that given year. The SCC is intended to provide a comprehensive measure of the monetized value of the net damages from global climate change from an additional unit of CO2, including, but not limited to, changes in net agricultural productivity, energy use, human health effects, and property damages from increased flood risk. Federal agencies use the SCC to value the CO2 emissions impacts of various policies including emission and fuel economy standards for vehicles, regulations of industrial air pollutants from industrial manufacturing, emission standards for power plants and solid waste incineration, and appliance energy efficiency standards.
Keywords: Environment and Environmental Studies

The Power of Change: Innovation for Development and Deployment of Increasingly Clean Electric Power Technologies - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Electricity, supplied reliably and affordably, is foundational to the U.S. economy and is utterly indispensable to modern society. However, emissions resulting from many forms of electricity generation create environmental risks that could have significant negative economic, security, and human health consequences. Large-scale installation of cleaner power generation has been generally hampered because greener technologies are more expensive than the technologies that currently produce most of our power. Rather than trade affordability and reliability for low emissions, is there a way to balance all three?
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Transportation Resilience: Adaptation to Climate Change - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Transportation Resilience: Adaptation to Climate Change and Extreme Weather Events summarizes a symposium held June 16–17, 2016 in Brussels, Belgium. The fourth annual symposium promotes common understanding, efficiencies, and trans-Atlantic cooperation within the international transportation research community while accelerating transport-sector innovation in the European Union (EU) and the United States.The two-day, invitation-only symposium brought together high-level experts to share their views on disruptions to the transportation system resulting from climate change and extreme weather events. With the goal of fostering trans-Atlantic collaboration in research and deployment, symposium participants discussed the technical, financial, and policy challenges to better plan, design, and operate the transportation network before, during, and after extreme and/or long-term climate events.
Keywords: Transportation and Infrastructure

Review of the U.S. Global Change Research Program's Update to the Strategic Plan Document - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Update to the Strategic Plan (USP) is a supplement to the Ten-Year Strategic Plan of the U.S. Global Change Research Program (USGCRP) completed in 2012. The Strategic Plan sets out a research program guiding thirteen federal agencies in accord with the Global Change Research Act of 1990. This report reviews whether USGCRP’s efforts to achieve its goals and objectives, as documented in the USP, are adequate and responsive to the Nation’s needs, whether the priorities for continued or increased emphasis are appropriate, and if the written document communicates effectively, all within a context of the history and trajectory of the Program.
Keywords: Environment and Environmental Studies

Enhancing Participation in the U.S. Global Change Research Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. As the understanding of global change has evolved over the past decades and as demand for scientific information on global change has increased, the USGCRP has increasingly focused on research that can inform decisions to cope with current climate variability and change, to reduce the magnitude of future changes, and to prepare for changes projected over coming decades. Overall, the current breadth and depth of research in these agencies is insufficient to meet the country's needs, particularly to support decision makers. This report provides a rationale for evaluating current program membership and capabilities and identifying potential new agencies and departments in the hopes that these changes will enable the program to more effectively inform the public and prepare for the future. It also offers actionable recommendations for adjustments to the methods and procedures that will allow the program to better meet its stated goals.
Keywords: Environment and Environmental Studies; Earth Sciences; Behavioral and Social Sciences

Science Literacy: Concepts, Contexts, and Consequences - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Science is a way of knowing about the world. At once a process, a product, and an institution, science enables people to both engage in the construction of new knowledge as well as use information to achieve desired ends. Access to science—whether using knowledge or creating it—necessitates some level of familiarity with the enterprise and practice of science: we refer to this as science literacy.
Keywords: Education

Attribution of Extreme Weather Events in the Context of Climate Change - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
As climate has warmed over recent years, a new pattern of more frequent and more intense weather events has unfolded across the globe. Climate models simulate such changes in extreme events, and some of the reasons for the changes are well understood. Warming increases the likelihood of extremely hot days and nights, favors increased atmospheric moisture that may result in more frequent heavy rainfall and snowfall, and leads to evaporation that can exacerbate droughts. Even with evidence of these broad trends, scientists cautioned in the past that individual weather events couldn't be attributed to climate change. Now, with advances in understanding the climate science behind extreme events and the science of extreme event attribution, such blanket statements may not be accurate. The relatively young science of extreme event attribution seeks to tease out the influence of human-cause climate change from other factors, such as natural sources of variability like El Niño, as contributors to individual extreme events. Event attribution can answer questions about how much climate change influenced the probability or intensity of a specific type of weather event. As event attribution capabilities improve, they could help inform choices about assessing and managing risk, and in guiding climate adaptation strategies. This report examines the current state of science of extreme weather attribution, and identifies ways to move the science forward to improve attribution capabilities.
Keywords: Earth Sciences; Environment and Environmental Studies

Characterizing Risk in Climate Change Assessments: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The U.S. Global Change Research Program (USGCRP) was established in 1990 to "assist the Nation and the world to understand, assess, predict, and respond to human-induced and natural processes of global change."1 A key responsibility for the program is to conduct National Climate Assessments (NCAs) every 4 years.2 These assessments are intended to inform the nation about "observed changes in climate, the current status of the climate, and anticipated trends for the future." The USGCRP hopes that government entities from federal agencies to small municipalities, citizens, communities, and businesses will rely on these assessments of climate- related risks for planning and decision-making. The third NCA (NCA3) was published in 2014 and work on the fourth is beginning.
Keywords: Environment and Environmental Studies

Next Generation Earth System Prediction: Strategies for Subseasonal to Seasonal Forecasts - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
As the nation's economic activities, security concerns, and stewardship of natural resources become increasingly complex and globally interrelated, they become ever more sensitive to adverse impacts from weather, climate, and other natural phenomena. For several decades, forecasts with lead times of a few days for weather and other environmental phenomena have yielded valuable information to improve decision-making across all sectors of society. Developing the capability to forecast environmental conditions and disruptive events several weeks and months in advance could dramatically increase the value and benefit of environmental predictions, saving lives, protecting property, increasing economic vitality, protecting the environment, and informing policy choices.
Keywords: Earth Sciences

Frontiers in Decadal Climate Variability: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Many factors contribute to variability in Earth's climate on a range of timescales, from seasons to decades. Natural climate variability arises from two different sources: (1) internal variability from interactions among components of the climate system, for example, between the ocean and the atmosphere, and (2) natural external forcings, such as variations in the amount of radiation from the Sun. External forcings on the climate system also arise from some human activities, such as the emission of greenhouse gases (GHGs) and aerosols. The climate that we experience is a combination of all of these factors.
Keywords: Earth Sciences

Addressing Significant Weather Impacts on Airports: Quick Start Guide and Toolkit - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Report 160: Addressing Significant Weather Impacts on Airports provides a web toolkit that raises airport operator awareness about vulnerabilities caused by significant weather events. The toolkit helps airports develop more robust contingency and recovery plans, in addition to their airport emergency plans. This toolkit focuses on events that are “rare but plausible”; that is, events that may have happened in the distant past, or in adjacent geographic areas, but are not common event types at the airport itself, and therefore may not be in the forefront of the airport managers’ minds. The Quick Start Guide provides guidance for using the toolkit.Disclaimers: The opinions and conclusions expressed or implied in this material are those of the researchers who performed the research. They are not necessarily those of the Transportation Research Board, the Academies, or the program sponsors. Materials noted with an asterisk (*) have been edited by TRB; otherwise, materials are as supplied by the contractor.Any digital files or software included is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB”) be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Our world is changing at an accelerating rate. The global human population has grown from 6.1 billion to 7.1 billion in the last 15 years and is projected to reach 11.2 billion by the end of the century. The distribution of humans across the globe has also shifted, with more than 50 percent of the global population now living in urban areas, compared to 29 percent in 1950. Along with these trends, increasing energy demands, expanding industrial activities, and intensification of agricultural activities worldwide have in turn led to changes in emissions that have altered the composition of the atmosphere.
Keywords: Earth Sciences